Shifting Responsibility Strategies: Apology in Saudi Arabia - صوري يالله, محمد; مسعد اللهيبي, فهد (Revues faculté des lettres et des langues; No 14-15 (2014): مجلة كلية الآداب واللغات, 2014)
لقد فحص هذا البحث طرق الاعتذار عند  370 من طلاب وطالبات المرحلة الجامعية في المملكة العربية السعودية الذين اختيروا من جامعات في  خمس مناطق مختلفة؛ لتحديد أنواع الاستراتيجيات المتسلسلة التي توظف في معظم الأحيان عند الاعتذار. اعتمدت الدراسة على ملاحظة التنوع المجتمعي ونسخة من فحص إنجاز الخطاب "DCT "، كتبت بالفصحى المعاصرة وتضمنت افتراض 12 حالة يقع فيها الطالب أو الطالبة أمام أشخاص تختلف مكانتهم الاجتماعية. وكشفت النتائج لكلا الطريقتين أن الثقافة السائدة في المملكة العربية السعودية  عند تقديم الاعتذار هي إما تحويل المسؤولية أو عدم ربطها بالمخطئ؛ فالسعوديون لا يحبذون الاعتذار المباشر   We examined the apologies of 370 Saudi Arabian undergraduate students proportionally selected from the five regional universities of the Kingdom to determine the types and sequencing of strategies they used most often to apologize.  The study relied on ethnographic observation and a version of the Discourse Completion Test “DCT,” written in Standard Arabic, that contained 12 hypothetical situations in which a student had committed violations involving people of different social parameters. The results revealed that apologies in Saudi Arabian culture typically shift responsibility away from the offender as Saudis do not like to apologize outright.